Global plagues and the Global Fund: Challenges in the fight against HIV, TB and malaria - Tan Darrell HS; Upshur Ross EG; Ford Nathan (BMC, 2003)
Abstract Background Although a grossly disproportionate burden of disease from HIV/AIDS, TB and malaria remains in the Global South, these infectious diseases have finally risen to the top of the international agenda in recent years. Ideal strategies for combating these diseases must balance the advantages and disadvantages of 'vertical' disease control programs and 'horizontal' capacity-building approaches. Discussion The Global Fund to Fight AIDS, Tuberculosis and Malaria (GFATM) represents an important step forward in the struggle against these pathogens. While its goals are laudable, significant barriers persist. Most significant is the pitiful lack of funds committed by world governments, particularly those of the very G8 countries whose discussions gave rise to the Fund. A drastic scaling up of resources is the first clear requirement for the GFATM to live up to the international community's lofty intentions. A directly related issue is that of maintaining a strong commitment to the treatment of the three diseases along with traditional prevention approaches, with the ensuing debates over providing affordable access to medications in the face of the pharmaceutical industry's vigorous protection of patent rights. Summary At this early point in the Fund's history, it remains to be seen how these issues will be resolved at the programming level. Nevertheless, it is clear that significant structural changes are required in such domains as global spending priorities, debt relief, trade policy, and corporate responsibility. HIV/AIDS, tuberculosis and malaria are global problems borne of gross socioeconomic inequality, and their solutions require correspondingly geopolitical solutions.